Factors influencing youth’s online purchasing intention / Mohamad Fidry Ahmad - Ahmad, Mohamad Fidry (Faculty of Business and Management, 2019)
Aim of this study is to investigate the factors that can be considered as important factor of youth’s online purchasing intention. Besides that, the objective of this study is to identify the most influential determinants of online shopping intention among youth’s. The independent variables of this study are consisting of perceived ease of use, perceived usefulness and perceived enjoyment. One hundred (100) respondents be collected using a google form. The primary data and secondary data also used to find information for supporting sampling technique. Furthermore, the researcher used questionnaire as the method to collect all the data from sample respondents in accomplishing the research objectives. The finding showed that perceived ease of use, perceived usefulness and perceived enjoyment has influence on online shopping intention among youth’s. Therefore, the three variables which is perceived ease of use, perceived usefulness and perceived ease of use show positive relationship towards the online shopping intention among youth’s. Lastly, discussion and recommendation have in the last of the research to improve the skill of future researcher, convenience sampling used in the research.